Profil Emisi Gas Rumah Kaca Di Kabupaten Sambas - Halim, Iqbal; Jati, Dian Rahayu; Sulastri, Aini (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Climate change is the phenomenon of increasing concentrations of greenhouse gases (GHG) in the Earth's atmosphere. Sambas Regency, the extreme coastal area of West Kalimantan, has a population of 647,800. It contributes to greenhouse gas emissions from various activities, such as transportation, waste management, agriculture, plantation, and animal husbandry. This research aims to calculate greenhouse gas emissions across multiple sectors, create an emissions map, and identify mitigation efforts. The study's results are expected to inform the Sambas Regency Government in designing mitigation actions that are easy to implement in the field. The method used to conduct this greenhouse gas emission inventory follows Tier-1 IPCC (Intergovernmental Panel on Climate Change) 2006 guidelines, with emission factors set to the IPCC standard. Activity data used in the emission inventory is sourced from secondary data. Meanwhile, mitigation options were generated from literature studies. The results showed that the total GHG emissions in the Agriculture sector in Sambas Regency reached 277.25 Gg CO2-eq, in the Plantation sector the total GHG emissions in the Palm Oil Plantation sector in Sambas Regency reached 13.40 Gg CO2-eq, the total GHG emissions in the transportation sector in Sambas Regency reached 228.20 Gg CO2-eq, the total GHG emissions in the Livestock sector in Sambas Regency reached 0.684 Gg CO2-eq. The total GHG emissions in the waste sector in Sambas Regency reached 0.0901 Gg CO2-eq.